The Iconic Stilation of Molioboro Street Furniture - Prasetiyo Yunianto (SULUH: Jurnal Seni Desain Budaya, 2018)
Malioboro street furniture becomes an important part in Yogyakarta’s pedestrian zone and the tourists’ activities there. The interesting part of the object is the unique identity which comes in the form of various motifes which are implemented in certain part of the several furniture objects like out door chair, and the pedestrian border line. The implemented motifes are chosen based on the iconic cultural object of Yogyakarta like Merapi Mountain, The Tree of Beringin Kurung, pedicab, carriage, and gunungan. Those motifes will be analyzed semiotically by elaborating the existed visual signs. The analysis is conducted to see how far the stilasi process occurs on the real object till it turns to be a motif. The analysis is also aimed to explore the meaning of the implemented motif by seeing its detail form. The result of the analysis shows that the stilasi process is done by simplifying the form of the chosen iconic cultural object which still exposes the main element of the object as the motif pattern. The process is completed by adding an ornamentic touch on the secondary object. The stilation process is presented with decorative nuance on the detailed part of every motif. Overall, the created motifes are sucessfully becoming an iconic representation and succeeding in giving informative values about Yogyakarta’s cultural object to the visitors.